Hidden Conditional Random Field with Distribution Constraints for Phone Classification - Acero, Alex; Deng, Li; Yu, Dong (Interspeech 2009, 2009)
We advance the recently proposed hidden conditional random field (HCRF) model by replacing the moment constraints (MCs) with the distribution constraints (DCs). We point out that the distribution constraints are the same as the traditional moment constraints for the binary features but are able to better regularize the probability distribution of the continuous-valued features than the moment constraints. We show that under the distribution constraints the HCRF model is no longer log-linear but embeds the model parameters in non-linear functions. We provide an effective solution to the resulting more difficult optimization problem by converting it to the traditional log-linear form at a higher-dimensional space of features exploiting cubic spline. We demonstrate that a 20.8% classification error rate (CER) can be achieved on the TIMIT phone classification task using the HCRF-DC model. This result is superior to any published single-system result on this heavily evaluated task including the HCRF-MC model, the discriminatively trained HMMs, and the large-margin HMMs using the same features.